Management of single submucosal fibroid in unmarried females with uterine artery embolization - Juneja, Sunil Kumar; Kaur, Gagandeep; Chaudhary, Muskan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Uterine fibroids (leiomyomas) are the most common benign neoplasm of the female pelvis. The location of fibroids, whether submucosal, subserosal, pedunculated subserosal, intramural, or endocavitary, is important because signs and symptoms may be determined by location. Uterine artery embolization (UAE) for many patients is an effective alternative treatment to surgical therapy for fibroid tumors. It is a minimally invasive procedure, which allows for rapid recovery and return to normal activities. Objective of this study was to know the efficacy of minimally invasive technique UAE for reducing symptoms in sub-mucous uterine leiomyoma in unmarried females. Methods: This retrospective analysis was performed on 9 unmarried females with symptomatic single submucosal fibroid diagnosed on MRI with size range of 3.5 cms to 6.5 cms. They presented at Dayanand Medical College and Hospital, Ludhiana, Punjab in a period of 3 years from January 2016-December 2019. Inclusion criteria were unmarried females, single submucosal fibroid diagnosed on USG/MRI. Exclusion criteria was active infection, more than one fibroid in uterus, prior GnRH analogues treatment during the previous 3 months. Results: All patients presented with heavy menstrual bleeding (HMB) and dysmenorrhea, lower abdomen pain was encountered in 3 patients and 2 patients had inter-menstrual bleeding. Recurrent, UTI was there in 1 patient and 1 patient had vaginal discharge. All fibroids belonged to stage 1 FIGO classification. UAE was done and patients were followed for 6 months. Symptomatic success was seen in 100% patients and 77.77% patients expelled the fibroid per vaginally. Conclusions: UAE is alternative method of treatment for submucosal fibroids in unmarried females who do not want to undergo surgery. Proper case selection can give us good results and symptomatic relief.